Pharmacokinetics and pharmacodynamics of intravenous midazolam in patients with severe alcoholic cirrhosis. Issue 2 (February 1986) - MacGilchrist, A J; Birnie, G G; Cook, A; Scobie, G; Murray, T; Watkinson, G; Brodie, M J
Abstract : Midazolam kinetics and psychomotor function were studied after an intravenous dose of 0.075 mg/kg body weight in seven patients with alcoholic cirrhosis and eight control patients. Four of the seven cirrhotics died of complications of their liver disease within six months of the study. The metabolism of midazolam was significantly impaired in the cirrhotic patients (p less than 0.025). These patients also had evidence of greater sedation than the control group for up to six hours after the dose was administered (p less than 0.05). The clearance of midazolam did not correlate significantly with the serum albumin, or bilirubin, or with the kinetics of antipyrine, or indocyanine green. This study shows significant delay in the elimination of midazolam and decreased psychomotor function in patients with severe alcoholic liver disease. Caution is needed in using this drug for premedication in such patients before endoscopy.